THE EFFECTS OF HORMONAL AND NON-HORMONAL INTRAUTERINE DEVICE CONTRACEPTIVE ON SOME PARAMETERS IN IRAQI WOMEN SERA - REHABJ. ALMANGUSHY; LAMIA A. ALMASHHEDY; BUSHRA J. ALRUBIEY (International Journal of Pharma and Bio Sciences, 2014)
This study included eighty healthy women, thirty women used copper bearing intrauterine contraceptive device (IUD), and twenty women used hormonal intrauterine device. Thirty women were used copper bearing intrauterine device (T380A) are group (1), and twenty women were used hormonal intrauterine device (mirena) which release progestin hormone are group (2). Thirty apparently healthy women were taken as a control group who are using male condom contraceptive (group 3), the duration of each contraceptive in these groups for at least 6 months. The mean of age for users of copper bearing IUDs is29.43± 7.92 years, the mean of age for hormonal-IUD (mirena) is 32.63± 8.14 years, and the mean of for the control group is 31.40 ± 9.82 years. Blood samples obtained from Babylon maternity and pediatric hospital in Hilla city and Karbala maternity hospital in Karbala city. The sera obtained from the blood fordeterminingthe effects of copper bearing IUD, and hormonal-IUD on malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), catalase and some trace elements(copper, zinc and iron) concentration. The result of the present research showed significant increase in MDA, SOD and copper concentration,nonsignificant decrease in zinc, significant decrease in iron, nonsignificant increase in BMI, nonsignificant decrease in GSH and catalase concentration in sera of women in group 1, when compared with group 3, also this research showed significant increase in MDA concentration, significant decrease in SOD, GSH, catalase, BMI is significant increase, nonsignificant increase in copper and zinc concentration, and nonsignificant decrease of iron in sera women of group 2 when compared to those of the group 3.